PROPOSISI BENTUK KOSONG DALAM WACANA SLOGAN: KAJIAN TINDAK TUTUR WACANA SLOGAN - Imam Suyitno (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2005)
Slogan is a striking and easily remembered statement or sentence used to advertise something or to make clear the aim(s) of group, organization, campaign, etc. The discourse consists of some propositions, but most are not explicitly uttered, called zero form propositions. Thus, slogan is a discourse that different from common discourses. Analysts or readers need to know the entire propsitions that constitute the slogan to understand what it means. They must understand the speech context and speech event that create and support the slogan. Therefore, a speech act approach is relevant to the analysis.